The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/0004-6256/135/6/2212
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity Analysis of the Radio Curve of PKS 1510-089 and Implications for Its Central Structure

Abstract: We have analyzed the radio light curves of PKS 1510-089 at 37 and 22 GHz from 1990 to 2005 taken from the database of the Metsähovi Radio Observatory, and find evidence of quasi-periodic outbursts. The light curves show great activity with very complicated non-sinusoidal variations. Using Jurkervich's method, the power spectrum method, and the discrete autocorrelation function to analyze these data, we have found two periods of p 1 = 0.92 ± 0.04 yr and p 2 = 1.82 ± 0.12 yr for the outbursts in PKS 1510-089. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
(53 reference statements)
3
24
0
Order By: Relevance
“…One notes that the period of T 1 =(1.80± 0.06) yr is in good agreement with the deep flux minima period of (1.84±0.1) yr observed in the optical bands by Wu et al and by Xie et al [7,10] . The period of T 1 =(1.80± 0.06) yr is in good agreement with the period of the outbursts of (1.82±0.12) yr obtained by Xie et al [9] , and they used the Jurkervich's method and the power spectrum method to analyze the radio band data. These results imply that the periods of the deep flux minima in PKS 1510-089 are in agreement with the periodicities of the outbursts, which show that the two periodic phenomena have a common physical origin.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…One notes that the period of T 1 =(1.80± 0.06) yr is in good agreement with the deep flux minima period of (1.84±0.1) yr observed in the optical bands by Wu et al and by Xie et al [7,10] . The period of T 1 =(1.80± 0.06) yr is in good agreement with the period of the outbursts of (1.82±0.12) yr obtained by Xie et al [9] , and they used the Jurkervich's method and the power spectrum method to analyze the radio band data. These results imply that the periods of the deep flux minima in PKS 1510-089 are in agreement with the periodicities of the outbursts, which show that the two periodic phenomena have a common physical origin.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, Xie et al analyzed the light curve at radio bands of 22 and 37 GHz by using the J-K method, the power spectrum density method and the DCF method, all the three methods' results are similar in periodic analysis, and they found that PKS 1510-089 had two periods P 1 =(0.92±0.04) yr and P 2 =2P 1 =(1.82±0.12) yr. But both of these periods were not confirmed in next observations [9] . In order to check these periodic variability, in this work we study the periodicity information in the radio historical light curves of PKS 1510-089 at 22 and 37 GHz using the wavelet analysis methods.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…The periodic variabilities of blazars have been investigated extensively in the optical band (e.g., Bai et al 1998Bai et al , 1999Fan & Lin 2000;Xie et al 2008;Li et al 2009;Urry 2011;King et al 2013;Zhang et al 2014;Bhatta et al 2016;Fan et al 2016). An interesting case is that of OJ 287, which has a ∼12 yr period cycle (Kidger et al 1992;Valtonen et al 2006).…”
Section: Introductionmentioning
confidence: 99%